Combination Therapy of Phage vB_KpnM_P-KP2 and Gentamicin Combats Acute Pneumonia Caused by K47 Serotype Klebsiella pneumoniae - Wang, Zijing; Cai, Ruopeng; Wang, Gang; Guo, Zhimin; Liu, Xiao; Guan, Yuan; Ji, Yalu; Zhang, Hao; Xi, Hengyu; Zhao, Rihong; Bi, Lanting; Liu, Shanshan; et al. (Frontiers in Microbiology, 2021)
Klebsiella pneumoniae (K. pneumoniae) is an important nosocomial and community acquired opportunistic pathogen which causes various infections. The emergence of multi-drug resistant (MDR) K. pneumoniae and carbapenem-resistant hypervirulent K. pneumoniae (CR-hvKP) has brought more severe challenge to the treatment of K. pneumoniae infection. In this study, a novel bacteriophage that specifically infects K. pneumoniae was isolated and named as vB_KpnM_P-KP2 (abbreviated as P-KP2). The biological characteristics of P-KP2 and the bioinformatics of its genome were analyzed, and then the therapeutic effect of P-KP2 was tested by animal experiments. P-KP2 presents high lysis efficiency in vitro. The genome of P-KP2 shows homology with nine phages which belong to “KP15 virus” family and its genome comprises 172,138 bp and 264 ORFs. Besides, P-KP2 was comparable to gentamicin in the treatment of lethal pneumonia caused by K. pneumoniae W-KP2 (K47 serotype). Furthermore, the combined treatment of P-KP2 and gentamicin completely rescued the infected mice. Therefore, this study not only introduces a new member to the phage therapeutic library, but also serves as a reference for other phage-antibiotic combinations to combat MDR pathogens.